Pengaruh Perilaku Belajar Siswa Dan Interaksi Teman Sebaya Terhadap Hasil Belajar Siswa Fase E Akuntansi Di SMK N 2 Padang - Resti Handayani; Dessyta Gumanti; Reni Respita (Kilau Publishing, 2025)
This study aims to analyze 1) the influence of student learning behavior on the learning outcomes of students in phase e of accounting at SMKN 2 Padang. 2) the effect of peer interaction on the learning outcomes of accounting phase e students at SMKN 2 Padang. 3) the influence of student learning behavior and peer interaction on the learning outcomes of accounting phase e students at SMKN2 Padang.This type of research is descriptive and associative research. The population in the study is phase e students at SMKN 2 Padang. Sampling was done using the Proportionar Random Sampling technique. So the amounted sample to 59 people. The instruments used for the study were in the form of a closed questionnaire using the Multiple Linear Regression test and ahypothesistestwiththet-test and the F test. The results of the study showed that: 1) There was a positive and significant influence between student learning behavior (X1) on the learning outcomes of students in phase e of accounting at SMKN 2 Padang. It is known that the regression coefficient value β the level of student learning behavior has a positive value of 0,142 and the calculated t-value is 3,540 > t table of 2,003 with a significant value of 0,001 < α = 0,05, 2) There is a positive and significant influence between peer interaction (X2) on the learning outcomes of students in phase e of accounting at SMKN 2 Padang. It is known that the value of the regression coefficient β peer interaction has a positive value of 0,095 and the calculated t-value of 2,620 > table t of 2,003 with a significant value of 0,011< α = 0,05, 3) There is an influence of student learning behavior (X1), and peer interaction (X2)stealthily on learning outcomes(Y).